Pengembangan Pendidikan Islam di Pondok Pesantren Al-Khairiyah Citangkil - Bahyati; Syafuri, B; Wasehudin (LPPM Universitas Ibn Khaldun, Bogor, 2024)
Islamic boarding schools are Islamic educational institutions that have been developing for a long time. In their development, these Islamic boarding schools have experienced rapid progress until now Salafi Islamic boarding schools and Modern Islamic boarding schools have been formed. The aim of this research is for future researchers to know the development of Islamic education at the Al-Khairiyah Islamic boarding school and how Islamic education is implemented in this place. This research uses qualitative research which includes observation or observing directly in the field. To strengthen this research, the author uses descriptive sentences originating from journals, books, and so on. This research was carried out at the Al-Khairiyah Citangkil Islamic Boarding School, Cilegon, Banten. It was concluded that the development of Islamic education at the Al-Khairiyah Islamic boarding school was carried out by reciting the Koran together, disciplining the students themselves, forming good character so that the students were well equipped for their future lives. Abstrak Pondok pesantren merupakan lembaga pendidikan Islam yang berkembang sejak dahulu, di dalam perkembangannya pondok pesantren ini mengalami kemajuan pesat hingga saat ini terbentuklah pondok pesantren salafi dan pondok pesantren Modern. Tujuan dari penelitian ini agar para peneliti selanjutnya mengetahui perkembangan pendidikan Islam di pondok pesantren Al-Khairiyah dan bagaimana pendidikan Islam itu dilaksanakan di tempat ini. Penelitian ini menggunakan penelitian kualitatif yang meliputi observasi atau mengamati langsung di lapangan, untuk memperkuat penelitian ini, penulis menggunakan kalimat deskriptif yang berasal dari jurnal-jurnal, buku, dan lain sebagainya. Penelitian ini dilaksanakan di Pondok Pesantren Al-Khairiyah Citangkil kota Cilegon Banten. disimpulkan bahwa perkembangan pendidikan Islam di pondok pesantren Al-Khairiyah ini dilaksanakan dengan cara mengaji bersama-sama, pendisiplinan pada diri santri, membentuk karakter yang baik agar para santri mendapatkan pembekalan yang baik untuk kehidupan yang akan mendatang.